(untitled) (gjstudies, 2019)
This research investigates the underexplored relationship between the qualitative dimensions of audit documentation and the outcomes of regulatory inspections, movingbeyond traditional compliance-focused metrics. While prior literature has predominantly examined documentation completeness and adherence to standards, this studyintroduces a novel framework for assessing documentation quality based on three original constructs: narrative coherence, evidential triangulation density, and professionaljudgment transparency. We argue that these qualitative attributes, which capture therichness and logical integrity of the audit reasoning process, are significant predictors of inspection outcomes, even when quantitative compliance metrics are satisfied.Utilizing a mixed-methods approach, we analyze a unique dataset of 150 audit engagements from financial institutions that underwent regulatory inspection between2000 and 2004. Our methodology involves a proprietary content analysis protocol toscore documentation against our new framework, coupled with regression analysis totest its predictive power on inspection findings. The results reveal that engagementswith higher scores in narrative coherence and professional judgment transparency areassociated with a 40% and 35% lower probability, respectively, of receiving significantadverse inspection findings, controlling for standard compliance scores and firm size.Furthermore, we find that evidential triangulation density moderates the relationshipbetween complex accounting estimates and inspection outcomes. These findings contribute original insights by demonstrating that the *quality of argumentation* withindocumentation, not merely its existence, is a critical determinant of regulatory perception and success. The study offers a new paradigm for audit practice, training,and regulatory evaluation, emphasizing the communicative and persuasive function ofdocumentation as a core component of audit quality